Assessing the reliability and validity of attitudes and confidence scales for the care of women and girls affected by female genital mutilation/cutting - Christina X. Marea; Nicole Warren; Nancy Glass; Crista Johnson-Agbakwu; Nancy Perrin (BMC, 2021)
Abstract Background Approximately 545,000 women and girls in the USA have undergone Female Genital Mutilation/ Cutting (FGM/C) or have mothers from a country where FGM/C is practiced. Women and girls living with FGM/C in the USA may experience stigma and bias due to their FGM/C, immigration, racial, and language status. Health care provider attitudes toward FGM/C and confidence for related clinical care may affect the quality of care, yet there are no validated instruments to measure these constructs. Methods We developed the instruments via review of the FGM/C literature, the development of scale items, expert review, and pre-testing. We validated the instruments using a convenience sample of providers in Arizona and Maryland. We used exploratory factor analysis (EFA) to confirm factor structures, and compared scores between known groups to assess validity. Results The EFA revealed a two-factor solution for attitudes, including subscales for Negative Attitudes and Empathetic Attitudes toward FGM/C and those who practice with Cronbach's alphas of 0.814 and 0.628 respectively. The EFA for confidence revealed a two-factor solution including Confidence in Clinical FGM/C Care and Confidence in Critical Communication Skills for FGM/C Care with Cronbach's alphas of 0.857 and 0.694 respectively. Conclusions Health care provider attitudes and confidence toward FGM/C care may affect quality of care and health outcomes for women and girls. Our study describes the rigorous psychometric analysis to create reliable and valid instruments to assess health care provider attitudes and confidence for the care of women and girls who have experienced FGM/C. Trial registration ClinicalTrials.gov , NCT03249649 . Registered on 15 August 2017. Retrospectively registered.